Prevalência e perfil de sensibilidade de Staphylococcus aureus resistentes à meticilina (MRSA) no Hospital Universitário de Santa Maria - Rodrigues, Mônica de Abreu (2013)
Methicillin-resistant Staphylococcus aureus (MRSA) are reported worldwide as a high prevalence of pathogens in the etiology of infections, both nosocomial and community. This study aimed to determine the prevalence of MRSA in the University Hospital of Santa Maria (HUSM), 2007-2011, as well as evaluating the sensitivity to vancomycin front of MRSA isolates collected from May to December 2011. We analyzed retrospectively the clinical data of all patients diagnosed with MRSA infections between January 2007 and December 2011. During this period, 1,852 samples of S. aureus foram isolated in HUSM, and 616 (33.3%) were resistant to oxacillin. There was a significant reduction in the prevalence rates of this pathogen which rose from 43.4% in 2007 to 33.9% in 2008, 30.4% in 2009, 28.1% in 2010 and 27.5% in 2011. Infections were more prevalent in male patients, aged 41 to 70 years, hospitalized in Medical clinic (16.28%), Adult Intensive Care Unit (15.13%), First Aid Post (13%), Adult Emergency Care (12.67%) and Surgery Clinic (12.5%). A greater isolation of MRSA in blood samples (16.9%), followed by tracheal aspirates (16.5%), urine (10.4%), sputum (8.7%), surgery wound secretion (8.1%) and lower limb secretion (7.8%). As for the determination of susceptibility to vancomycin, 125 samples from S. aureus were collected prospectively from May to December 2011, which 31 (24.8%) were MRSA. The minimum inhibitory concentration (MIC) of vancomycin was determined using a conventional methodology manual broth microdilution. The MIC most frequent among all S. aureus were the 1μg/mL, presented by 53.6% of the strains, whereas among MRSA, there was a higher frequency of MIC of 2 mg/mL (48.4%). Therefore all isolates belonging to this study were sensitive to this antimicrobial of choice for infections caused by MRSA strains. Thus, given the high rates of morbidity and mortality associated with these infections, this study demonstrated the importance of recognizing the prevalence and profile of susceptibility to vancomycin of MRSA so that effective measures for the treatment and control of MRSA to take effect.